EUROPEAN MACROECONOMIC DYNAMICS ON FINANCIAL MARKETS AND ECONOMIC POLICY: A CROSS COUNTRY STUDY FOR SPILLOVER EFFECTS - CIOCÎRLAN, Cecilia; ZWAK-CANTORIU, Maria-Cristina; STANCEA, Andreea; PLĂCINTĂ, Dimitrie-Daniel (Studia Universitatis Babeș-Bolyai Oeconomica, 2023)
What is the direction and extent of the spillover effects of sovereign bond yields in the European Union and which countries are transmitters and receivers of these effects? The motivation for this research is related to the need to better understand the interconnectedness of European Union sovereign bond markets in the context of rising budget deficits and public debt, as well as recent financial and sovereign debt crises, which have highlighted the importance of bond market interdependencies. The main objective of the paper is to investigate the direction and magnitude of the spillover effects of sovereign bond yields in the European Union and to identify the states that act as transmitters and receivers of these effects. The data used in the analysis include the evolution of the bond markets of the euro area member states and non-monetary union states, to allow comparison and assessment of their interconnectivity. To analyze the interconnectedness of bond markets, methods which provide a suitable analysis framework to assess volatility propagation between countries were used. The research results highlight that most of the contagion effects are concentrated in the peripheral countries, such as Romania, Portugal, Lithuania and Ireland, and the central countries act as transmitters of these effects. JEL Classification: C01, C51, C52, C53, C54, C58, C61, C63